Strategic analysis of the maintenance of a metal-mechanic manufacturing line based on equipment trustability calculation - Sellitto, Miguel Afonso (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper reports a strategic analysis performed on the maintenance of a production line, based on studies of systemic and isolated equipment reliability xx. It starts describing some characteristics of the use of reliability in industrial maintenance and then xx a case in manufacture, by applying reliability techniques in the formulation of strategies for factory maintenance. With basis on the obtained results, xx the method is strenghtened, xx the requirements for the application are pinpointed and the conclusions about the use of reliability as an underlying theory to the maintenance strategy formulation process are reached. Also, xx considerations linking manufacturing strategy goals with maintenance strategy goals are drawn, which in turn, must contribute to the obtainment of the enterprise’s business goals xx. Keywords: Maintenance strategy; Case study in maintenance; Reliability in industrial maintenance; Equipment reliability xx; Weibull analysis in maintenance.